EXERCISES AND TESTS IN ENGLISH ACADEMIC WRITING - Olena Yasynetska (Scientific Journal of Polonia University, 2024)
The aim of this paper is to disclose the critical domain of academic writing and its pivotal role in scholarly communication and professional achievement. The study seeks to evaluate the efficacy of a structured academic writing approach using a mixed-methods design, incorporating pre-test and post-test assessments alongside qualitative insights derived from the participant feedback. The participants underwent an initial pre-test covering the structural aspects of academic writing, followed by engagement in a structured undergraduate course emphasising specific nuances of academic papers and mastery of cohesive elements for academic and professional purposes. The qualitative aspect provided a nuanced understanding of the learners’ experiences and perceptions. The structured undergraduate course entailed practical activities and tests covering fundamental aspects of academic writing. These encompass understanding the intended audience and purpose, recognising conventions and standards, grasping the subtleties of formal tone and language precision, refining skills in evidence-based argumentation, analysing the organisational structure of academic texts, evaluating the effectiveness of thesis statements, and incorporating tasks related to professional writing. The research underscores the practical application of acquired academic writing skills, aligning them with professional purposes. Overall, the study aims to contribute valuable insights into the effectiveness of a structured academic writing approach in preparing individuals for success in both academic and professional contexts.